Decomposing Changes of Socioeconomic Inequality in Physical Activity between 2005 and 2015 in the U.S Using RIF Regressions - Liu, Tong (Université d'Ottawa | University of Ottawa, 2017)
This paper applies the RIF regression decomposition method to socioeconomic inequality in physical activity and extends the RIF method to health achievement index. Moreover, an Oaxaca-Blinder type decomposition is applied to the results of the RIF regression decompositions to estimate the relative contributions of various socioeconomic and demographic characteristics. Using the NHIS data on the general US population, we find positive evidence of an existing socioeconomic inequality which reduced in severity from 2005 to 2015. People with less social and human capital are found to experience more severe inequality on average.